دور الصلح في تحقيق السلم المجتمي - Alqahoom, Abdulhameed (Al-Zahra: Journal for Islamic and Arabic Studies, 2023)
The study aims to elucidate the role of social reconciliation in achieving public peace, distancing oneself from chaos, disorder, and the spread of corruption, which disrupt the balance within societies. This is accomplished through the concept of social peace, highlighting its objectives and legitimate necessities, as well as emphasizing the importance of reconciliation in its achievement. The study also examines the outcomes resulting from activating the role of reconciliation in achieving social peace.